Chimeric Antigen Receptors Based on Low Affinity Mutants of FcεRI Re-direct T Cell Specificity to Cells Expressing Membrane IgE - Ward, Dana E.; Fay, Brittany L.; Adejuwon, Adebomi; Han, Huihui; Ma, Zhengyu (Frontiers in Immunology, 2018)
IgE is the key mediator of allergic responses. Omalizumab, an IgE-specific monoclonal antibody that depletes IgE, is effective for treating severe allergic asthma. The need for frequent administration of the expensive drug, however, limits its applications. Taking advantage of T cell memory, adoptive T cell therapy (ACT) targeting IgE-producing cells has the potential to achieve long-term suppression of IgE and relief of symptoms for severe allergic diseases. The transmembrane form of IgE (mIgE), which is present on all IgE-producing cells, serves as an excellent molecular target for ACT that employs chimeric antigen receptors (CARs). Here, we designed and tested CARs that use the extracellular domain of high affinity IgE receptor, FcεRIα, for mIgE recognition. When expressed on Jurkat T cells, FcεRIα-based CARs mediated robust responses in terms of CD69 upregulation to U266 myeloma cells expressing low levels of mIgE. FcεRIα-based CARs specifically recognized cells expressing mIgE, but not cells with secreted IgE captured through Fcε receptors. CAR+ Jurkat cells did not respond to LAD2 mast cells with secreted IgE bound through FcεRI or Ramos cells with secreted IgE bound through FcεRII. Co-culture of CAR+ Jurkat cells and LAD2 mast cells with IgE bound did not trigger LAD2 cell degranulation. The activity of CAR using wild type FcεRIα for mIgE binding was inhibited by the presence secreted IgE, which likely blocked CAR-mIgE interaction. The activities of CARs using low affinity mutants of FcεRIα, however, tolerated secreted IgE at relatively high concentrations. Moreover, primary human CD8+ T cells expressing a low affinity mutant CAR responded to U266 cells with INFγ production and cytotoxicity despite the presence of secreted IgE. The potency, specificity, and robustness of our CAR design, combined with repaid advances in the safety of ACT, hold promise for novel and highly effective cell-based therapies against severe allergic diseases.